A Literatura Infanto-Juvenil E A Formação De Crianças Leitoras - Maciel, Martina Maria Campos (Universidade Federal do Tocantins, 2022)
This article proposes to emphasize the role of children's literature in the education of children readers, as well as addressing the importance of the habit of reading. In this sense, we highlight children's literature as a relevant educational aspect of great value, as it takes the child, in a pleasant way, to the knowledge of the world of information, fantasy, imagery, as well as the real, which will consequently reflect new knowledge. Reading is an important tool for the reader to build their knowledge and learn to exercise their citizenship. Thus, children's literature contributes to the formation and construction of individual, social and cultural development. This is a process that parents and teachers play fundamental roles to awaken in the child the habit and the pleasure of reading.